2007
DOI: 10.1111/j.1365-2621.2006.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential uses of composted olive oil waste

Abstract: Food industry will have to focus on waste avoidance as well as utilisation of process waste. Application of clean technologies greatly enhances the safety and quality of the product as well as reducing the energy requirements and environmental impact of the food industry. The main environmental impacts of the food sector are aquatic, atmospheric and solid waste emissions. Nowadays, the main treatment method of solid wastes is composting, while recovery and reuse of by-products and wastes as raw materials stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 58 publications
(102 reference statements)
2
43
0
2
Order By: Relevance
“…Composting typically removes the phytotoxicity of the residues within a few weeks and allows the subsequent enrichment of croplands with compost nutrients that were originally taken up by olive tree cultivation (Arvanitoyannis and Kassaveti 2007). Such a tight circulation and recycling of nutrients has a certain aesthetic and practical appeal, particularly in local situations where the small-scale production of oil by individual mills can re-utilise the wastes to improve subsequent cropping, be it olives or other produce such as tomatoes.…”
Section: Bioremediation Of Olive-mill Waste By Compostingmentioning
confidence: 99%
See 1 more Smart Citation
“…Composting typically removes the phytotoxicity of the residues within a few weeks and allows the subsequent enrichment of croplands with compost nutrients that were originally taken up by olive tree cultivation (Arvanitoyannis and Kassaveti 2007). Such a tight circulation and recycling of nutrients has a certain aesthetic and practical appeal, particularly in local situations where the small-scale production of oil by individual mills can re-utilise the wastes to improve subsequent cropping, be it olives or other produce such as tomatoes.…”
Section: Bioremediation Of Olive-mill Waste By Compostingmentioning
confidence: 99%
“…Composting of OMWs requires the proper adjustment of pH, temperature, moisture, oxygenation and nutrients, thereby allowing the adequate development of the microbial populations (Arvanitoyannis and Kassaveti 2007). In general, ideal conditions for an optimal composting process are a carbon-to-nitrogen ratio of the composting material between 20 and 40, moisture content between 50% and 65%, an adequate oxygen supply, a small particle size and enough void space through which air can flow (Chang et al 2006).…”
Section: Bioremediation Of Olive-mill Waste By Compostingmentioning
confidence: 99%
“…Studies in this regard pertaining to olive oil (Arvanitoyannis and Kassaveti, 2007;Arvanitoyannis et al, 2007aArvanitoyannis et al, , 2007bVlyssides et al, 2004), castor oil (Sivakumar et al, 2008) and palm oil (Reijnders and Huijbregts, 2008) have been reported earlier. Recently, production of bioparaffins by the catalytic hydrogenation of natural triglycerides (Hancsók et al, 2012) and sustainability and mitigation of greenhouse gases using ethyl beef tallow biofuel in energy generation (Pereira et al, 2012) have been reported.…”
Section: Oils/fats Treatment Processesmentioning
confidence: 92%
“…2-3 months. This can lead to soil and water pollution [18,19] unless appropriate life cycle management strategies are adopted, allowing a sustainable development of this important agro-food industry.…”
Section: Introductionmentioning
confidence: 99%